2019
DOI: 10.3390/f10090741
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of NAC Gene Family in Betula pendula

Abstract: NACs (NAM, ATAF1/2, and CUC2) are plant-specific transcription factors that play diverse roles in various plant developmental processes. In this study, we identified the NAC gene family in birch (Betula pendula) and further analyzed the function of BpNACs. Phylogenetic analysis reveals that the 114 BpNACs can be divided into seven subfamilies. We investigated the expression levels of these BpNACs in different tissues of birch including roots, xylem, leaves, and flowers, and the results showed that the BpNACs s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 92 publications
0
53
0
Order By: Relevance
“…To examine the phylogenetic relationship among VcNAC proteins, an unrooted phylogenetic tree was constructed with alignments of 158 VcNACs and 51 AtNACs. According to the structural similarity and conserved motifs, all of the NAC proteins were divided into 14 subgroups [11,35]. We found that…”
Section: Identification and Phylogenetic Analysis Of Nac Tfs In Bluebmentioning
confidence: 99%
“…To examine the phylogenetic relationship among VcNAC proteins, an unrooted phylogenetic tree was constructed with alignments of 158 VcNACs and 51 AtNACs. According to the structural similarity and conserved motifs, all of the NAC proteins were divided into 14 subgroups [11,35]. We found that…”
Section: Identification and Phylogenetic Analysis Of Nac Tfs In Bluebmentioning
confidence: 99%
“…In the process of genome evolution, tandem duplication and segmental duplication were the main factors that led to the expansion of gene family [35]. Certain studies have shown that tandem duplication was largely responsible for the expansion of birch gene family [33], such as tandem duplication are the main reason for the expansion of B. pendula NAC gene family [15]. By contrast, segmental duplication has contributed signi cantly to the expansion of this gene family in Pyrus bretschneideri [28].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the expression patterns of BpPODs in different tissues in Betula platyphylla × Betula pendula, we downloaded the sequencing data from the NCBI SRA database with an accession number of PRJNA535361 [15]. To identify the expression of BpPODs during cold treatment in Betula platyphylla × Betula pendula, we downloaded the sequencing data from the NCBI SRA database with an accession number of PRJNA532995 [15]. The clean reads of each sample were obtained by ltering out reads of low quality.…”
Section: Differential Expression Pro Le Of Bppod Gene Familymentioning
confidence: 99%
See 1 more Smart Citation
“…We downloaded the transcriptome data (PRJNA535361) [18] from the NCBI SRA database to investigate the expressional patterns of B. pendula cellulose synthase genes in different tissues. The clean reads of three replicates per tissues were aligned to the B. pendula transcriptome by using STAR v2.7.3a [19], and the accurate transcript quanti cation was estimated by using RSEM v1.3.3 (RNA-seq by Expectation-Maximization) pipeline [20] with paired-end sequencing mode.…”
Section: Rna-seq Expression Analysis Of B Pendula Cell Wall Synthesimentioning
confidence: 99%